A rapid supercritical water approach for one-pot synthesis of a branched BiVO4/RGO composite as a Li-ion battery anode - Rangappa, Dinesh; Manickavasakam, Karnan; Muniyappa, Murthy; Bekal, Chandrakantha; Satish, Shenoy B.; Misnon, Izan Izwan; Kandasamy, Manikandan; Shetty, Manjunath (Royal Society of Chemistry, 2024)
The application of novel one-dimensional (1D) architectures in the field of energy storage has fascinated researchers for a long time. The fast-paced technological advancements require reliable rapid synthesis techniques for the development of various Multi-metal oxide (MMO) nanostructures. For the first time, we report the synthesis of a single-phase hierarchical one-dimensional (1D) branched BiVO4-Reduced Graphene Oxide (BVONB/RGO) nanocomposite with different weight percent variations of RGO starting from 6, 12, 24, and 26 wt% using the supercritical water method (SCW). The affirmation of the sample characteristics is done through various nano-characterization tools that help in establishing the monoclinic crystal structure, and nano branch morphology along with its physical, and thermal characteristics. Further, the electrochemical behavior evaluations of the fabricated coin cells provide insights into the well-known superior initial cycle capacity of around 810 mA h g−1, showing the superior ability of BVONB structures in storing lithium-ions (Li-ions). Meanwhile, an improved cyclic performance of the pure BVONB/RGO with 260 mA h g−1 is evident after 50 cycles. Finally, the reported rapid single-pot SCW approach has delivered promising results in establishing a material process technique for multimetal oxides and their RGO nanocomposites successfully.